Micro-nano structured VNb9O25 anode with superior electronic conductivity for high-rate and long-life lithium storage. (30th August 2021) - Liang, Mingxing; Huang, Yongcong; Lin, Yuda; Liang, Guisheng; Huang, Cihui; Chen, Lan; Li, Jiaxin; Feng, Qian; Lin, Chunfu; Huang, Zhigao
Graphical abstract: Highlights: Micro-Nano Structured VNb9O25 composites with rich oxygen vacancies have been prepared via a facile method. Several effective strategies were used to unveil the conductivity enhancement and structure stabilization mechanism. The VNb9O25 anodes can deliver remarkably LIB performance especially with ultra-long cycling performance. Abstract: The oxygen vacancies and micro-nano structure can optimize the electron/Li + migration kinetics in anode materials for lithium batteries (LIBs). Here, porous micro-nano structured VNb9 O25 composites with rich oxygen vacancies were reasonably prepared via a facile solvothermal method combined with annealing treatment at 800℃ for 30 h (VNb9 O25 -30 h). This micro-nano structure can enhance the contact of active material/electrolyte, and shorten the Li + diffusion distance. The introduction of oxygen vacancies can further boosts the intrinsic conductivity of VNb9 O25 -30 h for achieving excellent LIB performance. The as-prepared VNb9 O25 -30 h anode showed advanced rate capability with reversible capacity of 122.2 mA h g −1 at 4 A g −1, and delivered excellent capacity retention of ∼100 % after 2000 cycles. Meanwhile, VNb9 O25 -30 h provides unexpected long-cycle life (i.e., reversible capacity of 165.7 mA h g −1 at 1 A g −1 with a high capacity retention of 85.6 % even after 8000 cycles). Additionally, coupled with the LiFePO4 cathode, the LiFePO4 //VNb9 O25 -30 h full cell delivers superior LIB properties with high reversible capacities of 91.6 mA h g −1 at 5C for 1000 cycles. Thus, such reasonable construction method can assist in other high-performance niobium-based oxides in LIBs.